2022
DOI: 10.1111/nmo.14482
|View full text |Cite
|
Sign up to set email alerts
|

Associations between postprandial symptoms, hydrogen and methane production, and transit time in irritable bowel syndrome

Abstract: Background: Abnormal oroanal transit time (OATT) and visceral hypersensitivity are key pathophysiological factors in irritable bowel syndrome (IBS). The lactulose nutrient challenge test (LNCT) has been developed to assess the postprandial symptoms and gut microbial fermentation. We aimed to investigate associations between OATT, rectal sensitivity, and LNCT in IBS patients. Methods:We included 263 IBS patients from two study cohorts, where the link between pathophysiology and symptoms was investigated. During… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…We recently found that increased CH 4 on breath test correlated with increased abundance of methanogens, including M. smithii , in stool samples from IBS-C subjects, and predicted microbial metabolic pathway analysis indicated enrichment of pathways associated with methanogenesis in these subjects [ 6 ]. These findings are also consistent with an independent study which recently found that increased CH 4 on breath test was associated with slower oroanal transit times in IBS subjects, whereas increased H 2 on breath test was associated with more rapid oroanal transit times [ 11 ]. In the present study, increased stool M. smithii levels correlated with a constipation-like phenotype (decreased stool % wet weights) in a rat model.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We recently found that increased CH 4 on breath test correlated with increased abundance of methanogens, including M. smithii , in stool samples from IBS-C subjects, and predicted microbial metabolic pathway analysis indicated enrichment of pathways associated with methanogenesis in these subjects [ 6 ]. These findings are also consistent with an independent study which recently found that increased CH 4 on breath test was associated with slower oroanal transit times in IBS subjects, whereas increased H 2 on breath test was associated with more rapid oroanal transit times [ 11 ]. In the present study, increased stool M. smithii levels correlated with a constipation-like phenotype (decreased stool % wet weights) in a rat model.…”
Section: Discussionsupporting
confidence: 92%
“…In a recent publication, we identified distinct gut microbial compositions and associated breath gas profiles in subjects with IBS-C vs. IBS-D, with increased breath CH 4 in IBS-C subjects that correlated with increased levels of methanogens, including M. smithii , in stool samples, whereas IBS-D subjects had increased breath levels of both hydrogen (H 2 ) and hydrogen sulfide (H 2 S) [ 6 ]. A recent study by Algera et al, found that increased breath CH 4 levels were associated with decreased oroanal transit times in IBS subjects, and while that study did not measure H 2 S levels, they did find associations between increased breath H 2 levels and increased oroanal transit times in IBS [ 11 ]. The authors proposed that these findings resulted from differences in gut microbial compositions in different groups of IBS subjects [ 11 ], which is consistent with our identification of distinct gut microtypes and breath gas profiles in IBS-C vs. IBS-D subjects [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that these patients have a much shorter oro-cecal transit time and hence a higher likelihood of having a false positive HBT. [38][39][40] This is due to the substrate reaching the cecum, before a higher exhaled hydrogen concentration is seen. Furthermore, many of the limitations of HBTs can be mitigated if they are combined with an independent measurement of orocecal transit (e.g., scintigraphy).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that patients who reported diarrhea and fluctuating bowel habit were more likely to have a positive HBT. Studies have shown that these patients have a much shorter oro‐cecal transit time and hence a higher likelihood of having a false positive HBT 38–40 . This is due to the substrate reaching the cecum, before a higher exhaled hydrogen concentration is seen.…”
Section: Discussionmentioning
confidence: 99%